Healthcare costs after kidney transplantation compared to dialysis based on propensity score methods and real world longitudinal register data from Sweden - Ye Zhang; Ulf-G. Gerdtham; Helena Rydell; Torbjörn Lundgren; Johan Jarl (Scientific Reports, 2023)
Abstract This study aimed to estimate the healthcare costs of kidney transplantation compared with dialysis using a propensity score approach to handle potential treatment selection bias. We included 693 adult wait-listed patients who started renal replacement therapy between 1998 and 2012 in Region Skåne and Stockholm County Council in Sweden. Healthcare costs were measured as annual and monthly healthcare expenditures. In order to match the data structure of the kidney transplantation group, a hypothetical kidney transplant date of persons with dialysis were generated for each dialysis patient using the one-to-one nearest-neighbour propensity score matching method. Applying propensity score matching and inverse probability-weighted regression adjustment models, the potential outcome means and average treatment effect were estimated. The estimated healthcare costs in the first year after kidney transplantation were €57,278 (95% confidence interval (CI) €54,467–60,088) and €47,775 (95% CI €44,313–51,238) for kidney transplantation and dialysis, respectively. Thus, kidney transplantation leads to higher healthcare costs in the first year by €9,502 (p = 0.066) compared to dialysis. In the following two years, kidney transplantation is cost saving [€36,342 (p < 0.001) and €44,882 (p < 0.001)]. For patients with end-stage renal disease, kidney transplantation reduces healthcare costs compared with dialysis over three years after kidney transplantation, even though the healthcare costs are somewhat higher in the first year. Relating the results of existing estimates of costs and health benefits of kidney transplantation shows that kidney transplantation is clearly cost-effective compared to dialysis in Sweden.